2000
DOI: 10.1074/jbc.275.1.378
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Analysis of the Primary Substrate Specificity Pocket of Complement Factor B

Abstract: Factor B is a serine protease, which despite its trypsin-like specificity has Asn instead of the typical Asp at the bottom of the S 1 pocket (position 189, chymotrypsinogen numbering). Asp residues are present at positions 187 and 226 and either one could conceivably provide the negative charge for binding the P 1 -Arg of the substrate. Determination of the crystal structure of the factor B serine protease domain has revealed that the side chain of Asp 226 is within the S 1 pocket, whereas Asp 187 is located o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 35 publications
1
11
0
2
Order By: Relevance
“…The esterolytic activity of the mutant is also substantially reduced compared with the wild‐type, mainly due to a reduction in the k cat value. These data indicate that residue D226 is the primary substrate determinant for P1‐Arg binding, and a proper registration of the long P1‐Arg side chain to D226 on one end and its scissile bond to the nucleophilic S195 on the other end is essential for efficient catalysis (Xu et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The esterolytic activity of the mutant is also substantially reduced compared with the wild‐type, mainly due to a reduction in the k cat value. These data indicate that residue D226 is the primary substrate determinant for P1‐Arg binding, and a proper registration of the long P1‐Arg side chain to D226 on one end and its scissile bond to the nucleophilic S195 on the other end is essential for efficient catalysis (Xu et al ., 2000).…”
Section: Resultsmentioning
confidence: 99%
“…As described, four of the six loops (loops 35, 60, 96 and 172) dictate the specificity at the S1′, S2′, S2 and S3 pockets. The atypical D226 residue in the S1 pocket determines P1‐Arg binding and catalysis (Xu et al ., 2000). The remaining structural motifs, which have no corresponding regions in all other SPs with known structures, raise intriguing questions regarding their functional roles.…”
Section: Discussionmentioning
confidence: 99%
“…In the human genome, the only examples are CFD, CFB, and a C1r-like serine protease, called C1r-LP. The aspartate residue at position 189 is replaced by serine residues in factor C2 and C1r-LP and by asparagine in CFB [43][44][45]. The C1r-related serine protease is synthesized as a complex-type zymogen and is able to cleave the haptoglobin precursor chain already very early in the ER after an arginine residue [44,46].…”
Section: The Structural Basis For New S1 Specificitiesmentioning
confidence: 99%
“…However, the crystal structures of factor B (Milder et al, 2007;Ponnuraj et al, 2004), C2 (Krishnan et al, 2007;Milder et al, 2006) and their individual domains (Bhattacharya et al, 2004;Xu et al, 2000), in combination with site-directed mutagenesis and enzyme kinetic studies, revealed some interesting structural details that correlate with both the narrow substrate specificity and the unique activating mechanisms of these enzymes. These findings revealed that the four essential structural features (Fig.…”
Section: Serine Proteases In Complement Activationmentioning
confidence: 99%